Pemanfaatan Sampah sebagai Bahan Dasar Pembuatan Media Pem-belajaran Matematika pada MI Al Iman Gunungpati Semarang (BERDAYA Indonesian Journal of Community Empowerment, 2021)
Meanwhile, Elementary School/Madrasah Ibtidaiyah (SD/MI) students are still in the concrete operational stage. In other words, SD/MI students can understand abstract mathematical objects through concrete objects. The use of mathematics learning media has proven to have many benefits in helping students learn and understand various important concepts in mathematics. On the other hand, MI Al Iman teachers, Gunungpati District, Semarang City, all of whom are classroom teachers, complained about the lack of availability of teaching aids used in the learning process. Assistance in the use of waste as a basic material for making mathematics learning media is expected to increase teacher creativity in order to improve the quality of education, especially in Mathematics. Utilization of waste is not only economical in terms of cost because it uses goods that are not used but can still be used, it is also intended to invite teachers and teach students to participate in efforts to conserve natural resources and the environment. Another benefit, the resulting learning media products can improve students' understanding in Mathematics Subjects.